The coronavirus disease 2019 main protease inhibitor from Andrographis paniculata (Burm.f) Ness - Sukardiman; Martha Ervina; Mohammad Rizki Fadhil Pratama; Hadi Poerwono; Siswandono Siswodihardjo (Wolters Kluwer Medknow Publications, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has attracted worldwide attention. Andrographis paniculata (Burm. f) Ness (AP) is naturally used to treat various diseases, including infectious diseases. Its Andrographolide has been clinically observed for anti-HIV and has also in silico tested for COVID-19 main protease inhibitors. Meanwhile, the AP phytochemicals content also provides insight into the molecular structures diversity for the bioactive discovery. This study aims to find COVID-19 main protease inhibitor from AP by the molecular docking method and determine the toxicity profile of the compounds. The results obtained two compounds consisting of flavonoid glycosides 5,4'-dihydroxy-7-O-β -D-pyran-glycuronate butyl ester and andrographolide glycoside 3-O-β-D-glucopyranosyl-andrographolide have lower free binding energy and highest similarity in types of interaction with amino acid residues compared to its co-crystal ligands (6LU7) and Indinavir or Remdesivir. The toxicity prediction of the compounds also reveals their safety. These results confirm the probability of using AP phytochemical compounds as COVID-19 main protease inhibitors, although further research must be carried out.